2021
DOI: 10.1136/postgradmedj-2021-139939
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-6 and severe disease and mortality in COVID-19 disease: a systematic review and meta-analysis

Abstract: BackgroundSo far, SARS-CoV-2 is the seventh coronavirus found to infect humans and cause disease with quite a strong infectivity. Patients diagnosed as severe or critical cases are prone to multiple organ dysfunction syndrome, acute respiratory distress syndrome and even death. Proinflammatory cytokine IL-6 has been reported to be associated with the severity of disease and mortality in patients with COVID-19.ObjectiveThis systematic review and meta-analysis were carried out to evaluate the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 92 publications
4
44
0
5
Order By: Relevance
“…Others have reported a link between elevated IL6 and IL10 levels to fatality (Li et al, 2021) providing external validation of our data collected from leftover blood samples. However, these factors alone are not sufficient for prediction of outcome (Liu et al, 2021b). Our study also revealed CCL20 as a key correlate of fatal COVID-19.…”
Section: Ll Open Access Isciencementioning
confidence: 51%
“…Others have reported a link between elevated IL6 and IL10 levels to fatality (Li et al, 2021) providing external validation of our data collected from leftover blood samples. However, these factors alone are not sufficient for prediction of outcome (Liu et al, 2021b). Our study also revealed CCL20 as a key correlate of fatal COVID-19.…”
Section: Ll Open Access Isciencementioning
confidence: 51%
“…Moreover, IL-6 is thought to be involved in COVID-19-associated coagulopathy through the generation of tissue factors and thrombin, stimulation of platelet activation, and induction of endothelial dysfunction [17] , [18] , [19] , [20] . Previous studies have demonstrated that serum levels of IL-6 are increased in patients with severe COVID-19, which is significantly correlated with adverse clinical consequences, including admission to the intensive care unit (ICU), ARDS, and death [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of COVID-19 severity remains unclear, numerous studies have shown an increase in the level of IL-6 and other proinflammatory cytokines in COVID-19 hospitalized patients and its association with the severity of the disease and mortality [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%